Experimental study on lateral instability of submarine pipelines in sandy seabed - Shun LU; Shuming YAN; Xiaodong ZHOU; Zhiqiang CAO; Hui JIN (You-qi chuyun)
Objective In complex and unpredictable marine settings, submarine pipelines laid in sandy seabeds are susceptible to lateral instability. Nonetheless, the reasons behind this remain ambiguous. Consequently, investigating the coupling mechanisms of various influencing factors that contribute to the lateral instability process of these pipelines under ocean current loads becomes crucial, encompassing hydrodynamic loads and pipeline-soil interactions. Methods Multi-type model experiments were conducted, using the independently designed mechanical loading experimental setups that included two constraint conditions to respectively prevent pipeline rolling and allow free movement at both ends. The experimental results were leveraged to delve into the physical mechanisms behind the lateral instability of submarine pipelines. Additionally, an analysis was conducted to reveal the impacts of a range of factors on the ultimate lateral soil resistance exerted on these pipelines and the lateral soil resistance coefficient, including underwater gravity, the pipelinesoil friction coefficient, the initial embedment depth ratio of pipelines, various types of sandy soils, and the end constraints applied to the submarine pipelines. Results The lateral soil resistance was observed to gradually increase until reaching its peak, as the horizontal displacement of the pipeline expanded. Correspondingly, the lateral soil resistance coefficient decreased gradually stabilized ultimately, with the pipeline experiencing increasing underwater gravity. The lateral soil resistance coefficient of the anti-rolling pipeline rose with higher friction factors. In contrast, the friction factor had minimal impact on the lateral soil resistance coefficient of the pipeline in free movement. The lateral soil resistance coefficient of the anti-rolling pipeline significantly exceeded that of the pipeline with both ends free. The initial embedment depth ratio of the anti-rolling pipeline notably affected the maximum settlement and the location of ultimate lateral soil resistance. Conclusion The pipeline-soil interactions under ocean currents showcase the dynamic coupling involving ocean currents, pipelines, and seabeds. This paper elucidates the development law of ultimate lateral soil resistance throughout the lateral instability process of pipelines under ocean current loads. The findings offer technical insights to support the design, laying, and safe operation of submarine pipelines.